The health perceptions, dengue knowledge and control willingness among Dai ethnic minority in Yunnan Province, China - Hui Liu; Cheng-Jiang Fang; Jian-Wei Xu (BMC, 2021)
Abstract Background Outbreaks of dengue fever are often found among Dai ethnical communities along China-Myanmar border. The objective of this study was: 1) to investigate residents' health perceptions, knowledge and control willingness to participate in dengue control and 2) to identify factors associated with control willingness among the Dai ethnic community. Methods This is a mixed method study of a cross-sectional design, in which qualitative in-depth interviews and quantitative household questionnaire surveys are included. Results Questionnaire was administered to 261 household heads, and in-depth interview was conducted with 18 key informants. Of them, many participants (70%, 182/259) and 12 key informants (66.7%) from the two rural communities believed that the Lord Buddha would protect the good people. Majority of the participants (81.4%, 206/253) knew that fever was one of dengue fever symptoms and most of them (82.2%, 213/259) indicated that mosquitoes could transmit dengue fever. However, only one third of the participants (30.1%, 78/259) indicated the perceived susceptibility of dengue fever, and only a half of them (50.2%, 130/259) indicated the perceived severity of dengue fever. Multivariate logistic analysis (MLA) indicated that the participants with family wealth index (FWI) 4-5 (OR: 22.9728; 95%CI: 2.4257-217.5688, p = 0.0063) were more likely to turn containers upside down (TCUD) compared to those with FWI 1-3; and the participants in the urban community (OR: 0.0239; 95%CI: 0.0019-0.3032, p = 0.004) were less likely to TCUD compared to those in the two rural communities. Around one third of the participants (36.8%, 96/239) reported that they were willing to seek treatment first for dengue fever from public health facilities. The MLA identified that the participants with the perceived severity of dengue fever (OR: 5.0564; 95%CI: 2.0672-12.3683, p = 0.0004), and with beliefs of sound hygiene helpful to people's health (OR: 11.5671; 95%CI: 2.0505-65.2502, p = 0.0055) were more likely to seek treatment first for dengue fever from the public health facilities. Conclusion The study finds that most of Dai people have sound knowledge. However, health educational interventions should target to promote the perceived susceptibility and the perceived severity of dengue fever among Dai people.